Breakfast in bed - Alers, Rochelle (Alers, Rochelle. Innkeepers., 2017)
Sometimes you go in search of a new beginning. Other times, it finds you. Tonya Martin enjoys her job as a professional chef for a Wall Street bank, her East Harlem walk-up, and the freedom to live and love by her own rules - right up until the day she finds herself suddenly downsized. But a spontaneous trip to New Orleans opens up a new opportunity. With time on her hands and her daughter soon graduating college, Tonya has the chance to reach for her own long-cherished dream - opening a restaurant on her friend Hannah's beautiful Garden District estate. While Hannah and her new husband work on transforming the DuPont House into a luxury inn, Tonya explores local cuisine, taking an apprentice role at famed restaurant Chez Toussaints. Gage Toussaint's mix of Creole, Cajun, and African ancestry is deeply attractive, and the sexy chef clearly wants their friendship to become much more. Drawn to him yet hesitant given their previous unhappy marriages, Tonya wonders if it's too late to leap into love again. Could Gage be just the ingredient she needs to make this delicious new life complete?